Hormonal therapy for menopause and breast-cancer risk by histological type: a cohort study and meta-analysis. - Reeves, G; Beral, V; Green, J; Gathani, T; Bull, D (2006)
BACKGROUND: Little information is available on how the risk of breast cancer associated with the use of hormone therapy for menopause varies by histological type. We aimed to describe such associations for eight histological types of breast cancer. METHODS: Analyses are based on 1 031 224 postmenopausal women recruited in 1996-2001 into a nationwide UK cohort study, and followed for incident cancer and death. Relative risks associated with use of hormone therapy were estimated for eight histological types of breast cancer. FINDINGS: During 3.6 million person-years of follow-up, 14 102 breast cancers were diagnosed, of which 13 782 (98%) had histological type recorded: 11 869 (86%) were invasive, including 8007 ductal, 1526 lobular, 365 mixed ductal-lobular, 492 tubular, 71 medullary, and 148 mucinous cancers; and 1913 (14%) were in situ, including 1443 ductal and 86 lobular cancers. The relative risks of invasive breast cancer in current users compared with never users of hormone therapy varied significantly according to tumour histology overall (p<0.0001), for users of oestrogen-only therapy (p=0.0001), and for users of oestrogen-progestagen therapy (p<0.0001). The largest relative risks in current compared with never users of hormone therapy were seen for lobular (relative risk 2.25, 95% CI 2.00-2.52), mixed ductal-lobular (2.13, 1.68-2.70), and tubular cancers (2.66, 2.16-3.28). The relative risks for ductal and mucinous cancers were 1.63 (95% CI 1.55-1.72) and 1.58 (1.08-2.31), respectively. The risk of medullary cancer was not increased (0.74, 0.43-1.28). The relative risk of in-situ disease in current users compared with never users of hormone therapy also varied significantly according to histological type (p=0.03), with a relative risk for lobular carcinoma in situ of 2.82 (1.72-4.63) and 1.56 (1.38-1.75) for ductal carcinoma in situ. The effects of hormone therapy on invasive ductal, lobular, and tubular cancer were generally greater for oestrogen-progestagen therapy than for oestrogen-only therapy, and were attenuated with increasing body-mass index (BMI). INTERPRETATION: The risks associated with use of hormone therapy for menopause differ by histological type of breast cancer, and are substantially attenuated with increasing BMI.